Understanding the Difference in Various Fractions of Serum Bilirubin while Estimated by Wet Chemistry and Dry Chemistry Method and its Importance in Neonatal Jaundice - Kaushal Kishor Singh; Kalpana Singh; Mala Kumar (Indian Journal of Medical Biochemistry)
Aim: The aim of this study is to find out the percentage of variation of bilirubin values in neonates by two different techniques: Dry chemistry versus wet chemistry method, and also to establish that unconjugated bilirubin ≠ indirect bilirubin and conjugated bilirubin ≠ direct bilirubin. Materials and methods: This comparative study was conducted over a period of 6 months from October 2019 to March 2020. Ethical approval was taken from Institutional Ethical Committee. Informed and written consent were taken from the parents of the enrolled neonates. A total of 195 blood samples were randomly collected from neonates (<14 days) admitted with neonatal hyperbilirubinemia in Department of Pediatrics for estimation of serum bilirubin fractions by two techniques, i.e., traditional wet chemistry and dry chemistry. The statistical analysis of data was performed by using software package SPSS version 16 and Microsoft Excel 2019. Results: In our study, mean total bilirubin measured by dry chemistry method Total bilirubin (TBild), neonatal bilirubin (BuBc/NBil) estimated by dry chemistry method, and total bilirubin estimated by wet chemistry method (TBilw) were 12.42 mg/dL, 12.21 mg/dL, and 11.72 mg/dL, respectively. Conclusion: Total bilirubin estimated by dry and wet chemistry methods differ due to difference in the principle of methods by which they are estimated in laboratories. Neonatal bilirubin (BuBc/NBil) may be preferred over total bilirubin estimated by wet chemistry as dry chemistry is estimating unconjugated and conjugated fractions of bilirubin, while in wet chemistry, direct bilirubin is estimated and indirect bilirubin is calculated. Hence, the term unconjugated bilirubin cannot be interchanged with indirect bilirubin and conjugated bilirubin as direct bilirubin. Clinical significance: Measurement of serum bilirubin among neonates with hyperbilirubinemia is an essential part for diagnosis and monitoring of neonatal jaundice. Both dry and wet chemistry methods correlated well, any method can be used for measurement of bilirubin, but switching the method while monitoring serum bilirubin levels during treatment must be discouraged.